The Stable, San Luis Obispo Mission - Howard Clinton Tibbitts::::::photographer:::
Back of postcard reads: 'Founded in 1772, this mission has passed through many experiences, and but little is left of the original mission.' Photographer may be H.C. Tibbitts.